Successful MitraClip™ implantation in a 15-year-old patient with multiple prior cardiac surgeries - Gorenflo, Matthias; Katus, Hugo; Bekeredjian, Raffi (Cardiology in the young, 2013)
Percutaneous edge-to-edge mitral valve repair using the MitraClipTM has not been used in children. The patient in this reported case was a 15-year-old male adolescent who presented postnatally with severe aortic valve stenosis and dysplasia of the mitral valve. The boy underwent surgical valvuloplasty at the age of 3 months and an aortoventriculoplasty with three re-operations. At the age of 15 years, he developed severe mitral valve regurgitation. Owing to high surgical risks, a MitraClipTM was implanted with a reduction of mitral regurgitation from grade 4+ to 2+, translating into a rapid clinical improvement.
Gesehen am 05.04.2018